The Analysis of Sharia Financial Management and Risk Factors on Business Sustainability in Fintech Lending in East Java - Lely Fitri Mardiana; Arief Yuswanto Nugroho (STIEKOP MALANG PRESS, 2026)
Purpose – This study aims to examine the influence of Sharia-compliant financial management practices on the business sustainability of Fintech Lending companies in East Java, Indonesia, while investigating the moderating role of operational, credit, and regulatory risks in this relationship. Design/methodology/approach – This study employed a quantitative research design using a structured questionnaire administered to 250 employees and managers of registered Sharia Fintech Lending platforms in East Java. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the relationship between Sharia financial management practices, business sustainability, and the moderating effects of identified risk factors. Findings – The findings demonstrate that Sharia-compliant financial management practices, including profit-sharing mechanisms (Mudharabah/Musharakah), asset-backed financing (Murabahah), and the avoidance of riba and gharar, have a significant positive effect on business sustainability. Furthermore, operational, credit, and regulatory risks significantly moderate the relationship, weakening the positive effect of Sharia financial management on sustainability. These results indicate that effective Sharia-based financial management contributes to long-term viability, but its effectiveness depends substantially on the organization's ability to manage various forms of risk. Research limitations/implications – This study is limited to registered Sharia Fintech Lending companies in East Java and relies primarily on cross-sectional survey data, which may limit the generalizability of the findings and the ability to capture long-term changes in business sustainability. Future research could employ longitudinal designs and include additional factors such as technological capability, customer trust, cybersecurity, financial literacy, and regulatory compliance. Originality/value – This study contributes to the emerging literature on Islamic fintech by integrating Sharia-compliant financial management and multiple risk dimensions into a comprehensive model of business sustainability. Its originality lies in empirically examining the moderating effects of operational, credit, and regulatory risks within the relatively under-researched Sharia Fintech Lending sector in Indonesia. The findings provide both theoretical and practical value by demonstrating that sustainable Sharia fintech development requires not only compliance with Islamic financial principles but also robust and integrated risk management practices.